Austria : Financial Sector Assessment Program Update Technical Note; Factual Update and Analysis of the IAIS Insurance Core Principles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This technical note highlights Austria's analysis of the International Association of Insurance Supervisors Insurance Core Principles. The Austrian economy generally performed well over the past several years, with growth above the euro-area average, falling unemployment, and low inflation. The Financial Market Authority (FMA) should investigate the use of market-based soundness indicators. Following the recent reorganization of bank supervision responsibilities, the FMA insurance supervisors will need to work even closer with the Oesterreichische Nationalbank (OeNB) in supervising financial groups.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet